Export variety and human capital distribution - Lim, Grace Hui Qi (2011)
This paper provides evidence that a country’s human capital distribution has an impact on its export variety of differentiated products. In this paper, we used US imports from 41 countries across the globe – Asia, the Americas, Europe and Australia – to estimate the export variety of differentiated products (as classified by Rauch’s classification) for each (differentiated) product exported by the 41 countries to the US. We also used internationally comparable test scores from the OECD Programme for International Student Assessment (PISA) to derive a proxy for human capital distribution. Our results show that for high income countries, the more diverse their workforce is, the higher the export variety of differentiated products while for low income countries, the less diverse their workforce is, the higher the export variety of differentiated products.